2016
DOI: 10.1007/jhep04(2016)168
|View full text |Cite
|
Sign up to set email alerts
|

Exact solution of Chern-Simons-matter matrix models with characteristic/orthogonal polynomials

Abstract: We solve for finite N the matrix model of supersymmetric U(N ) Chern-Simons theory coupled to N f fundamental and N f anti-fundamental chiral multiplets of R-charge 1/2 and of mass m, by identifying it with an average of inverse characteristic polynomials in a Stieltjes-Wigert ensemble. This requires the computation of the Cauchy transform of the Stieltjes-Wigert polynomials, which we carry out, finding a relationship with Mordell integrals, and hence with previous analytical results on the matrix model. The s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…They showed that the thermal partition function is given by 0trueZL×N=scriptQi<jsinh2()μiμj2i=1NcoshL()μi2eLtrueγμi2i=1Ndμi,where γ>0 is a positive parameter and the normalization constant scriptQ is 0truescriptQ=2Li<jsinh2()μiμj2i=1NeLtrueγμi2i=1Ndμi.It is interesting to point out that the sinh term in the above integrals also appears in the study of matrix models in Chern‐Simons‐matter theories; for example, see Refs. and .…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 97%
“…They showed that the thermal partition function is given by 0trueZL×N=scriptQi<jsinh2()μiμj2i=1NcoshL()μi2eLtrueγμi2i=1Ndμi,where γ>0 is a positive parameter and the normalization constant scriptQ is 0truescriptQ=2Li<jsinh2()μiμj2i=1NeLtrueγμi2i=1Ndμi.It is interesting to point out that the sinh term in the above integrals also appears in the study of matrix models in Chern‐Simons‐matter theories; for example, see Refs. and .…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 97%
“…In particular, the tools used in [15] for Chern-Simons-matter (CSM) matrix models directly apply here, and they do so in a much simpler fashion, since the term cosh L (µ i /2) can be understood as a characteristic polynomial insertion in the matrix model (2.3), which is a Stieltjes-Wigert ensemble [14]. This insertion, in contrast to the ones in [15], is in the numerator and hence the solution is directly in terms of Stieltjes-Wigert polynomials, and not their Cauchy transform. As a matter of fact, after a simple rewriting, some of the relevant computations are contained in much earlier work [23], since to study averages of Schur polynomials in the ensemble (2.3), we computed first the averages of correlation functions of characteristic polynomials in the ensemble (2.3).…”
Section: The Modelmentioning
confidence: 99%
“…where S N (λ) denotes the monic Stieltjes-Wigert polynomial [14,23,15] of degree N and S (k) N (λ) its k-th derivative. The explicit expression for the orthonormal SW polynomials [23,15] is…”
Section: Exact Solutionmentioning
confidence: 99%
See 2 more Smart Citations